Investigating the Structure‐Reactivity Relationships Between Nicotinamide Coenzyme Biomimetics and Pentaerythritol Tetranitrate Reductase. Issue 1 (6th October 2021) - Tan, Zhuotao; Han, Yaoying; Fu, Yaping; Zhang, Xiaowang; Xu, Mengjiao; Na, Qi; Zhuang, Wei; Qu, Xudong; Ying, Hanjie; Zhu, Chenjie
Abstract: Ene reductases (ERs) are attractive biocatalysts in terms of their high enantioselectivity and expanded substrate scope. Recent works have proved that synthetic nicotinamide coenzyme biomimetics (NCBs) can be used as easily accessible alternatives to natural cofactors in ER‐catalyzed reactions. However, the structure‐reactivity relationships between NCBs and ERs and influence factors are still poorly understood. In this study, a series of C‐5 methyl modified NCBs were synthesized and tested in the PETNR‐catalyzed asymmetric reductions. The physicochemical properties of these NCBs including electrochemical properties, stability, and kinetic behavior were studied in detail. The results showed that hydrophobic interaction caused by the introduced methyl group contributed to the stabilization of binding conformation in enzyme active site, resulting in comparable catalytic activity with that of NADPH. Molecular dynamics and steered molecular dynamics simulations were further performed to explain the binding mechanism between PETNR and NCBs, which revealed that stable catalytic conformation, appropriate donor‐acceptor distance and angle, as well as free dissociation energy are important factors affecting the activity of NCBs. Abstract :